Designing of disparity map based on hierarchical dynamic programming using satellite stereo imagery - Qayyum A.; Malik A.S.; Naufal M.; Saad M.; Mazher M.; Rasheed W.; Abdullah T.A.R.B.T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Biomedical engineering; Electric lines; Electric power systems; Electric utilities; Image acquisition; Image matching; Poles; Satellite imagery; Satellites; Stereo image processing; Students; Vegetation; Disparity map; Dynamic programming algorithm; Electricity distribution companies; High-voltage power line; IKONOS satellite; Ikonos satellite image; Stereo matching algorithm; Transmission poles; Dynamic programming